Analisis Faktor-Faktor Yang Mempengaruhi MinatPembelian Konsumen Retail(Studi Empiris Retail Konvensional Relasi Jaya Kartasura &Retail Modern Indomart Kleco Kartasura) - Ma'munah, Siti Ulfatul, M. Sholahuddin., SE., M.Si (2017)
This study aims to analyze some of the factors that influence consumer purchase interest in modern retail stores and conventional. Based on the results of this study are expected to provide input for retail Relationships Jaya in Kartasura and Indomart Kleco Kartasura in improving the quality of service to consumers and other factors affecting consumer purchase interest. Testing the hypothesis in this study using regression analysis moderating with t-test, F and coefficient of determination (R2). The population in this study are all the people who ever make transactions or purchases in relation Jaya Kartasura and Indomart Kleco. The sample in this study as many as 100 people and the goal is that everyone who ever made a purchase in relation Jaya Kartasura and Indomart Kleco. Based on the survey results revealed that Influence the location of the consumer purchase interest acquired tcount of 2.155 with p = 0.037. Therefore tcount greater than t table (2.155> 1.985) and p <0.05; then H1 is accepted, which means that the location of a significant effect on consumer purchase interest on Conventional Retail Relations Jaya Kartasura & Retail Modern Indomart Kleco Kartasura. The effect of price on consumer purchase interest acquired tcount of 3.843 with p = 0.000. Therefore tcount greater than t table (3.843> 1.985) and p <0.05; then H2 is accepted, which means that the price significantly influence consumer purchase interest on Conventional Retail Relations Jaya Kartasura & Retail Modern Indomart Kleco Kartasura. Impact of service quality to consumer purchase interest acquired tcount of 3.099 with p = 0.003. Therefore tcount greater than t table (3.099> 1.985) and p <0.05; the H3 is received, which means that service quality significantly influence consumer purchase interest on Conventional Retail Relations Jaya Kartasura & Retail Modern Indomart Kleco Kartasura. Influence range of products to the consumer purchase interest acquired tcount of 3.380 with p = 0.001. Therefore tcount greater than t table (3.380> 1.985) and p <0.05; the H4 is accepted, which means that the range of products significantly influence consumer purchase interest on Conventional Retail Relations Jaya Kartasura & Retail Modern Indomart Kleco Kartasura.